Des savoirs locaux aux experts naturalistes - Myriam Thirot; Pierre Failler; Justin Daniel (Revue d'ethnoécologie)
This paper presents the results of a research project conducted in 2016 with fishermen based in the north west of Martinique, Caribbean. Semi-directing interviews led face-to-face by a sociologist provided elements of the fishermen empirical knowledge relating to marine ecosystems, the interdependence of their various components, as well as their knowledge on the resilience of marine protected areas ecosystems regarding global changes.According to the anthropology of conservation and in a perspective of integrated resources management, the analysis focuses on local knowledge of fishermen of marine and coastal biodiversity. Based on daily observations, the marine ecosystem is analysed, by the fishermen, like a complex system submitted to a multifactorial reality, which demonstrates their naturalists and cognitive knowledge (species, oceanography, climatology and hydrology). The services provided by the fishermen can this be subject to a reward such as a payment for environmental services.